ANALISIS SISTEM KERJA DAN PERAWATAN ANDON DI PT. SHOETOWN KASOKANDEL INDONESIA - Suprayogi, Ogi; Dewi Jannati, Eidelweis (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
On a the shoe factory often happenned downtime (production stop), less response from the mechanic or team leader. The problem, can be overcome by andon, andon is a system monitoring and panel audio visual from electric useful to fast on information to mechanic or team leader, the system andon work when it happenned a problem at production. This study aims to analiyze the system and care in andon directly in field because comapny in demand to fulfill a request from buyer. The research method is by means of a survey directly to the factory area and the result of direct interviews of resourch persons and operators that are contained in the plant. After doing research 8 hours usage/ day andon relieve the operator to contact the team leader and technicians concerned if quality problems occur and damage to the machine.